Programa saberes indígenas na escola: avaliação de possibilidades e limites na construção de uma formação docente para um ensino diferenciado, intercultural e bilíngue, Lábrea-AM - (:unkn) unknown (Universidade Federal do Amazonas, 2019)
This research has as its object of study the Program “saberes Indígenas na Escola: Possibilidades e limites na construção de uma formação docente para um ensino diferenciado, intercultural e bilíngue” (Indigenous knowledge at school: Possibilities and limits in the construction of teacher education for a differentiated, intercultural and bilingual education). The main purpose of this study is to evaluate how the Indigenous Knowledge Program in school has been developed in the context of indigenous school education in the municipality of Lábrea -Amazonas from 2018 to 2019. Although we are guided, since we were born with a non-formal education, the school context must be linked to our reality, and so we have an interpretation and meaning in the act of learning. In this sense, this research will be based on the context of the theoretical framework in line with the methodological process of content analysis and finalized with bibliographic and field research, using observation and interview as instruments. We consider that this research may be pertinent, as it talks about reflections necessary to the approaches of considerable elements to the educational process of the indigenous peoples. Indigenous knowledge and values inserted in schools in indigenous education must be understood in a reflexive and necessary way to support transformative paths in the schooling processes. To guide the research, we approached authors such as Grupioni, Baniwa, Brazil, Candau, Munduruku and others. By reading these authors, we subsidized the contributions that emerged in the interview applied to indigenous teachers in the Marahã area to understand the anxieties and difficulties they face. We also sought to identify the ideologies of teachers' conceptual thoughts and what impact these contexts have on the formation of the teaching and learning process. It characterized the process of school education and training from the perspective of Karl Marx Theory, an essential premise for the total basis of the premises that ideologically alienate the thinking and performance of PSIE course teachers. This synthesis defends the understanding of the reality of man as a reflection of the lived historical conditions, in which the conditioned ideas of the systems are produced as a natural awareness of the real life process of Brazilian citizens. Therefore, the formation of indigenous teachers must be linked to the essence of a differentiated, intercultural and bilingual education, in order to revitalize or resignify the identity of traditional peoples. Empowering pedagogical support and understanding of the specific curriculum and according to the real needs of each people. Keywords: Public Policies. Indigenous school education; Teacher Training; Southern Amazon.
Keywords: Professores - Formação; Índios - Educação; Escolas indígenas - Amazonas (Estado); CIÊNCIAS HUMANAS; Políticas pública; Educação escolar indígena; Formação Docente, Sul do Amazonas